52 additional reference population samples for the 55 AISNP panel. (November 2015) - Pakstis, Andrew J.; Haigh, Eva; Cherni, Lotfi; ElGaaied, Amel Ben Ammar; Barton, Alison; Evsanaa, Baigalmaa; Togtokh, Ariunaa; Brissenden, Jane; Roscoe, Janet; Bulbul, Ozlem; Filoglu, Gonul; Gurkan, Cemal; et al.
Highlights: Commercial sequencing kits now available for the Kidd Lab set of 55 AISNPs. ALFRED and FROG-kb now have 125 reference population samples for these SNPs. Improved global coverage for reference populations. Abstract: Ancestry inference for a person using a panel of SNPs depends on the variation of frequencies of those SNPs around the world and the amount of reference data available for calculation/comparison. The Kidd Lab panel of 55 AISNPs has been incorporated in commercial kits by both Life Technologies and Illumina for massively parallel sequencing. Therefore, a larger set of reference populations will be useful for researchers using those kits. We have added reference population allele frequencies for 52 population samples to the 73 previously entered so that there are now allele frequencies publicly available in ALFRED and FROG-kb for a total of 125 population samples.